Evaluating the Student Training Equity Project: An Upstream Recruitment Approach to Diversifying Clinical Psychology Graduate Programs - Hannah Joseph; Mary Fernandes; Meghan Goyer; Maria Arce; Ciera Lewis; Claudia Delbasso; Suzann Lawry; Corey Walker; Omolade Amole; Mikael Sampson; Erin Tone (Georgia Educational Researcher, 2022)
The U.S. psychology workforce is considerably less diverse than the population that it serves. While several recruitment and admission practices are effective for diversifying psychology training programs, upstream recruitment of underrepresented candidates is particularly promising. Aiming to diversify the clinical psychology graduate program applicant pool, the Student Training Equity Project (STEP) was developed to promote and evaluate upstream recruitment of undergraduate students of color interested in psychology graduate studies. This study used a mixed-method design to evaluate immediate outcomes for three STEP programmatic strategies. Survey results suggest that STEP networking events were associated with undergraduate research and mentorship opportunities. Findings suggest that STEP funding supported students in producing research products (e.g., manuscripts) that might bolster graduate application materials. STEP website engagement data showed over 1,000 views per year, and highlighted ways to improve outreach. More controlled evaluation is needed to determine whether STEP contributed to diversification of the applicant pool.